Maternal alcohol consumption and the risk of miscarriage in the first and second trimesters: A systematic review and dose–response meta‐analysis - Kristina Rantzau Saxov; Katrine Strandberg‐Larsen; Sofie G. Pristed; Niels Henrik Bruun; Ulrik Schiøler Kesmodel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction According to a precautionary principle, it is recommended that pregnant women and women trying to conceive abstain from alcohol consumption. In this dose–response meta‐analysis, we aimed to examine the association between alcohol consumption and binge drinking and the risk of miscarriage in the first and second trimesters. Material and methods The literature search was conducted in MEDLINE, Embase and the Cochrane Library in May 2022, without any language, geographic or time limitations. Cohort or case–control studies reporting dose‐specific effects adjusting for maternal age and using separate risk assessments for first‐ and second‐trimester miscarriages were included. Study quality was assessed using the Newcastle–Ottawa Scale. This study is registered with PROSPERO, registration number CRD42020221070. Results A total of 2124 articles were identified. Five articles met the inclusion criteria. Adjusted data from 153 619 women were included in the first‐trimester analysis and data from 458 154 women in the second‐trimester analysis. In the first and second trimesters, the risk of miscarriage increased by 7% (odds ratio [OR] 1.07, 95% confidence interval [CI] 0.96–1.20) and 3% (OR 1.03, 95% CI 0.99–1.08) for each additional drink per week, respectively, but not to a statistically significant degree. One article regarding binge drinking and the risk of miscarriage was found, which revealed no association between the variables in either the first or second trimester (OR 0.84 [95% CI 0.62–1.14] and OR 1.04 [95% CI 0.78–1.38]). Conclusions This meta‐analysis revealed no dose‐dependent association between miscarriage risk and alcohol consumption, but further focused research is recommended. The research gap regarding miscarriage and binge drinking needs further investigation.